FACTORS AFFECTING AUDIT ENGAGEMENT DECISION - Fibriani, Rudiana (JEA17: Jurnal Ekonomi Akuntansi, 2022)
The study was conducted to examine and analyze whether audit risk, independence, Public Accounting Firm business risk, and client's business risk affect the decision to accept audit engagements. The data analysis method used is quantitative analysis with data collection techniques using questionnaires. 97 respondents are partners in an accounting firm in Surabaya. The results of this study are audit risk, auditor independence, and client business risk have a significant effect on audit engagement decisions. While the KAP business risk has a positive but not significant effect on audit engagement decisions.